Kajian Hidro-Oseanografi Untuk Rehabilitasi Suaka Margasatwa Muara Angke – Jakarta Utara - Asep Irwan (JOURNAL OF APPLIED SCIENCE (JAPPS), 2021)
Muara Angke Wildlife Reserve (MAWR) is the smallest natural reserve area in Indonesia with a wetland ecosystem type, dominated by open swamp and mangroves, and greatly influenced by freshwater from the Angke River. Although small, this region plays an important role in protecting biodiversity, especially for mangrove ecosystems in Jakarta. However, this area has suffered severe degradation because of river pollution and decreasing salinity so that rehabilitation efforts carried out to maintain the presence of mangrove ecosystems. We asses the hydro oceanographic aspects, i.e. tidal conditions, sedimentation and bathymetry by conducting field survey and modeling. Based on the results, there is 0.35 m increase in the water level compare to previous period. The value of Formzhal 2.47 is obtained which indicates the mixed tide prevailing diurnal type, mainly because of the influence of the river, although sometimes their mixed tides with very different heights and periods. The tidal mounts in Muara Angke based on the Admiralty method are 0.94 meters. Then, from the results of the sediment test, it was found the type of mud sediment with a value of TSS between 23 mg/l - 74 mg/l. The result of this study is that the sustainability of the mangrove ecosystem in Muara Angke Wildlife Reserve depends on these three aspects. There needs to be mitigation efforts to reduce sedimentation and overcome freshwater immersion from rivers so that mangrove rehabilitation in this region can be successful.